(untitled) - Gill, Stephen (New York, 1988)
It is a very thorough from a historical materialist perspective. A good book for reference as the chapters are spit up into topics that usually run two pages in length. The only problem with this piece would lie in the fact that it is almost a decade old.
Keywords: Economics